2008
DOI: 10.2353/ajpath.2008.070522
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Heat Stress-Induced Up-Regulation of Occludin Protein Expression

Abstract: The heat stress (HS)-induced increase in occludin protein expression has been postulated to be a protective response against HS-induced disruption of the intestinal epithelial tight junction barrier. The aim of this study was to elucidate the cellular and molecular processes that mediate the HS-induced up-regulation of occludin expression in Caco-2 cells. Exposure to HS (39°C or 41°C) resulted in increased expression of occludin protein; this was preceded by an increase in occludin mRNA transcription and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 54 publications
7
62
0
1
Order By: Relevance
“…As early as 8 to 12 h, these authors reported occludin protein expression to be increased in Caco-2 cells while ZO-1 is decreased. Additionally, occludin expression in Caco-2 cells exposed to 41°C was increased as early as 4 h while ZO-1 started to decrease at 6 h (Dokladny et al, 2008). These data suggest that changes in mRNA abundance of tight junction proteins due to HS may be more related to the protein phenotype than transcriptional.…”
Section: Discussionmentioning
confidence: 52%
“…As early as 8 to 12 h, these authors reported occludin protein expression to be increased in Caco-2 cells while ZO-1 is decreased. Additionally, occludin expression in Caco-2 cells exposed to 41°C was increased as early as 4 h while ZO-1 started to decrease at 6 h (Dokladny et al, 2008). These data suggest that changes in mRNA abundance of tight junction proteins due to HS may be more related to the protein phenotype than transcriptional.…”
Section: Discussionmentioning
confidence: 52%
“…There is compelling data to support a direct link between liver HSP70 accumulation and altered survival and inflammatory cytokine profile seen in heat-conditioned animals undergoing endotoxin stress. Human peripheral blood macrophages overexpressing HSP70 also inhibited lipopolysaccharide induced production of TNF-, IL-1 , IL-10 and IL-12 (Ding et al, 2001;Dokladny et al, 2008). These data taken as a whole demonstrates, that HSP70 expression is sufficient to alter proinflammatory cytokine production and increase endotoxin tolerance.…”
Section: Intracellular Heat Shock Proteins -Antinflammatory Moleculesmentioning
confidence: 61%
“…31,32 HSPs also maintain junctional proteins that are responsible for intestinal wall integrity, thus preventing endotoxin release from the intestine which is a main contributor of the heat shock response. 42 HSPs also enhance immune function while providing resistance against inflammatory cytokines.…”
Section: 36mentioning
confidence: 99%